EFEKTIVITAS AFIRMASI TENAGA KESEHATAN PADA TINGKAT KECEMASAN IBU BERSALIN MULTIPARA DI RSUD BULA KABUPATEN SERAM BAGIAN TIMUR TAHUN 2018/2019 - Triana Indrayani; Wiji Sumarni (Jurnal Ilmu dan Budaya, 2019)
Background: When anxiety influence mother's mind, the intervention more likely to  appear, this is due to the increase of the adrenal hormone that makes mother feel scared, trauma arises and the trigger of the heaviest stress in the hypothalamus. It was estimated that in 2015, WHO said that problems about the death among women during and after the delivery can be prevented. Aim: To find out the effectiveness of health workers selfaffirmation in the anxiety level of multiparous maternal mothers RPH Bula, East Side of Seram Regency in 2018/2019. Method: This research used quasi experiment, pre and post-test with control group design, which comparing one or more group experiments that are given a treatment on one comparing group and the other group without a treatment. The sample was 40 people.  Result : The frequency distribution of respondents had the dominant age of 28 years old  amounted to 75%, with normal birth history amounted to 75% and SC labor amounted to 25%, high school education as the majority of respondents  amounted to 85%, while the results of bivariate data that had significant differences in anxiety level scores before and after being given self-affirmation in the experimental group (Pvalue = 0,000), there was no significant difference in the anxiety level scores before and after the control group (Pvalue = 1.00). Conclusions and Suggestions: Self-affirmation was effective to the anxiety level, and health workers  especially midwives to further optimize the delivery of positive information to patients, giving applied technology regarding the level of anxiety to patients.